4CPS-237 Feasibility of continuous administration of antimicrobials in hospital: nothing is ever as it seems?. (14th March 2021) - Grootaert, V; Bigler, K; Bervoet, A; Van Praet, J; Nulens, E
Abstract : Background and importance: Continuous infusion (CI) of antimicrobials is increasingly applied because of the pharmacokinetic and practical advantages, including the rapid achievement of stable target serum concentrations, ease of sampling as levels are determined during steady state and simple interpretation of therapeutic drug monitoring. Aim and objectives: To assess medication administration practices related to CI of antimicrobials. Material and methods: During a 10 day prospective observational survey in March 2019, we enrolled all consecutive hospitalised non-ICU patients who received at least one antimicrobial suitable for CI. Amoxicillin, aztreonam, benzylpenicillin, ceftazidime, flucloxacillin, meropenem, piperacillin/tazobactam, temocillin and vancomycin were included as antimicrobials. Catheter type, number of lumens, administration mode, loading and maintenance dose, and pump settings were assessed by comparing the electronic prescription and patient file with the observations. Drug incompatibilities (DI) were analysed using the compatibility information provided in Trissel's two clinical pharmaceutics database and categorised as compatible, incompatible, uncertain or none. DI were defined as incompatibility or uncertainty about the compatibility between at least two simultaneously Y site administered drugs. Results: 107 observations in 86 patients were performed and 113 antimicrobial prescriptions were analysed. Peripheral lines were most commonly used (53%), followed by central venous catheters (35%) and peripherally inserted central catheters (10%). Single, double, triple and quadruple lumen catheters accounted for 56%, 23%, 17% and 4%, respectively. CI therapy was prescribed, according to hospital guidelines, in 96% of patients, 93% of whom received a loading dose. In 96% of cases a correct maintenance dose was administered. Only 63% of the infusion bags/syringes were labelled appropriately. In 7% of the observations, the pump settings did not match the prescribed dose, causing both over and under dosing in three patients (defined as >105% and <95% of the prescribed daily dose, respectively). We observed DI in 28% (30/107) of cases, mostly with single lumen catheters (63%), and in haematological patients (37%). Moreover, change from CI to intermittent infusion was the only solution to overcome DI in 73% of these cases. Conclusion and relevance: We found that administration issues were common in CI of antimicrobials. In response, we started educational sessions, the hospital policy was slightly adapted, including allowing intermittent infusion in the case of DI, and we created a prescribing alert for the assistance of a clinical pharmacist for DI review. References and/or acknowledgements: Conflict of interest: No conflict of interest